Kritik Sosial dalam Karya Sastra Bentuk Nyata Protes Sastrawan - Neneng Wahyuni (Jurnal KIBASP (Kajian Bahasa, Sastra dan Pengajaran), 2019)
The purpose of this study is to describe social criticism, a real form of man of letters protest against social problems throughher/his literary media. The method used is descriptive method. The results of this study found that Wisran Hadi and Athur S. Nalan conveyed their dislike of social phenomena through drama scripts. This is what is meant by the real form of literary protests through his work. Wisran Hadi through the drama drama"Jalan Lurus"describes his criticisms ranging from individual problems to his own character, to government issues. Whereas Artur S. Nalan through his draft text entitled Sobrat outlined which criticized the depravity of morals and a mindset that did not develop from humans, who were more interested in other regions even though in his area he could live better. In addition, moral problems are the actions of humans who no longer know what is good and what is bad. Conclusion, in general they describe their dislike of human habits in carrying out their lives. Keywords: Criticims,Drama, Protest.